Formal contracts, relational contracts, and the threat-point effect - Hideshi Itoh; Hodaka Morita (Center for Economic Studies and ifo Institute (CESifo), 2011)
Can formal contracts help resolving the holdup problem? We address this important question by studying the holdup problem in repeated transactions between a seller and a buyer in which the seller can make relation-specific investments in each period. In contrast to previous findings, we demonstrate that writing a simple fixed-price contract based on product delivery is of value even when relation-specific investment is purely cooperative. In particular, there is a range of parameter values in which a higher investment can be implemented only if a formal fixed-price contract is written and combined with an informal agreement on additional payments or termination of future trade, contingent upon investments. Furthermore, we show that under an additional natural assumption, focusing our attention on fixed-price contracts as a form of formal contracts is without loss of generality. The key driving force of our result is a possibility that the threat-point effect is negative, i.e., the relation-specific investment decreases the surplus under no trade. This possibility, although very plausible, has been largely ignored in previous theoretical/empirical analyses of the holdup problem.
Keywords: D23; D86; L14; L22; L24; 330; holdup problem; formal contract; relational contract; cooperative investment; fixed-price contract; relation-specific investment; repeated transactions; long-term relationships; Unvollständiger Vertrag; Vertragstheorie; Sunk Costs; Wiederholte Spiele; Theorie